Aritas : First Slovene Triennial of Satire and Humour. - Caks, Joze; Jagodic, Stane; Juric, Evgen; Menase, Lev; Volfand, Joze; Aritas : First Slovene Triennial of Satire and Humour, Smarje '95 (Celje : FIT-Media, 1995)
Rogelj, Bine ; Messner, Janko ; Mihelic, France ; Jeraj, Zmago ; Ciuha, Joze ; Tutta, Klavdij ; Cerne, Peter ; Boljka, Janez ; Makuc, Vladimir ; Jagodic, Stane ; Demsar, Tone ; Kaljanac, Enver ; Zorman, Alojz ; Zupancic, Lilijana Praprotnik ; Mancek, Marjan ; Kos, Bozo ; Sosic, Branko ; Novak, Andrej ; Hocevar, Marko ; Pecar, Borut ; Antic, Ivo ; Senica, Drago ; Vrhovec, Vili ; Kohek, Miran ; Primozic, Aljana ; Korelc, Leo ; Fuchs, Matjaz ; Panic, Bozidar ; Kuralt, Boris ; Cjuha, Mitja ; Kadmus, J. Mrkalj - ; Gorsic, Niko ; Petan, Zarko ; Cec, Franci ; Jagodic, Stane ; Juric, Evgen ; Smit, Joze ; Tof, Tone Fornezzi - ; Volaric, Joze ; Ringbauer, Rudi ; Milic, Jolka ; Schwentner, Bojan ; Skorjak, Bostjan ; Petelin, Joze ; Logar, Matija ; Breza, Tomo Kunovic - ; Klemencic, Janez ; Bradac, Marjan ; Buttolo, Albin ; Zupancic, Lilijana Praprotnik ; Kos, Iztok ; Matè, Miha ; Cimerman, Ivan ; Torkar, Igor ; Luzan, Pavel ; Maurer, Neza ; Rainer, Meta ; Cigler, Peter ; jr., Andrej Grampovcan ; Makuc, Andrej ; Messner, Janko ; Kurent, Tine ; Kolaric, Andrej ; Cebasek, Iztok ; Repe, Borivoj ; Francic, Franjo ; Korosec, Ivanka ; Smolcnik, Jerica ; Volaric, Zlata ; Svajncer, Janez ; Papler, Albert ; Born, Adolf ; Zlatkovsky, Mikhail M. ; Zabransky, Vlasta ; Sakai, Sadao ; Delhaye, Dominique
biografie
Aritas : First Slovene Triennial of Satire and Humour, Smarje '95
Engels
boek
Keywords: Slovenië